2017
DOI: 10.18632/oncotarget.20065
|View full text |Cite
|
Sign up to set email alerts
|

Discovery and evaluation of triple inhibitors of VEGFR-2, TIE-2 and EphB4 as anti-angiogenic and anti-cancer agents

Abstract: Receptor tyrosine kinases (RTKs), especially VEGFR-2, TIE-2, and EphB4, play a crucial role in both angiogenesis and tumorigenesis. Moreover, complexity and heterogeneity of angiogenesis make it difficult to treat such pathological traits with single-target agents. Herein, we developed two classes of multi-target RTK inhibitors (RTKIs) based on the highly conserved ATP-binding pocket of VEGFR-2/TIE-2/EphB4, using previously reported BPS-7 as a lead compound. These multi-target RTKIs exhibited considerable pote… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(20 citation statements)
references
References 34 publications
0
20
0
Order By: Relevance
“…30 In a recent study, the multitarget receptor tyrosine kinase inhibitor of VEGFR-2, TIE-2, and EphB4 QDAU5 was shown to mediate antiangiogenesis and anticancer activity in vitro and an in vivo MCF-7 breast cancer xenograft model. 31 In conclusion, the anti-EFNA4 ADC PF-06647263 evaluated in this study has shown manageable safety and a favorable PK profile at the RP2D administered once weekly. Although preliminary evidence of antitumor activity was observed in patients with heavily pretreated TNBC and ovarian cancer, study enrollment was terminated due to the limited response to adequate exposure of PF-06647263 in patients with TNBC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…30 In a recent study, the multitarget receptor tyrosine kinase inhibitor of VEGFR-2, TIE-2, and EphB4 QDAU5 was shown to mediate antiangiogenesis and anticancer activity in vitro and an in vivo MCF-7 breast cancer xenograft model. 31 In conclusion, the anti-EFNA4 ADC PF-06647263 evaluated in this study has shown manageable safety and a favorable PK profile at the RP2D administered once weekly. Although preliminary evidence of antitumor activity was observed in patients with heavily pretreated TNBC and ovarian cancer, study enrollment was terminated due to the limited response to adequate exposure of PF-06647263 in patients with TNBC.…”
Section: Discussionmentioning
confidence: 64%
“…Initial phase I findings with JI‐101 combined with everolimus in patients with advanced ovarian cancer showed that combination treatment was well tolerated, but associated with limited antitumor activity in this patient population . In a recent study, the multitarget receptor tyrosine kinase inhibitor of VEGFR‐2, TIE‐2, and EphB4 QDAU5 was shown to mediate antiangiogenesis and anticancer activity in vitro and an in vivo MCF‐7 breast cancer xenograft model …”
Section: Discussionmentioning
confidence: 99%
“…Type I 1/2 inhibitors interact with the same site as type I and extend to target the back pocket. VEGFR‐2, Tie‐2, and EphB4 share a basic architecture for construction, namely the hinge region, gatekeeper region, conserved Glu‐ and DFG‐motifs, and selective site . We have developed a novel multiple RTKI (BPS‐7) matching to the active site of these RTKs …”
Section: Multiple Rtkis As Antiangiogenic Agentsmentioning
confidence: 99%
“…VEGFR-2, Tie-2, and EphB4 share a basic architecture for construction, namely the hinge region, gatekeeper region, conserved Glu-and DFG-motifs, and selective site. 192 We have developed a novel multiple RTKI (BPS-7) matching to the active site of these RTKs. 193 Type I inhibitors bind to RTKs through one to three hydrogen bonds with the hinge region and hydrophobic interactions in the adenine ring domain.…”
Section: Structural Analysis Of Multitarget Inhibitorsmentioning
confidence: 99%
“…[ 28 ] Furthermore, the analysis of the X‐ray structure of various inhibitors bound to VEGFR‐2 confirmed the sufficient space available for various substituents around the terminal heteroaromatic ring. [ 29–31 ]…”
Section: Introductionmentioning
confidence: 99%